IMPLEMENTATION OF ANDROID-BASED MEDIA SMART WITH PNEUMATICS V.1.0 IN PNEUMATIC CONTROL SYSTEM LEARNING - Ibrahim, fakhri; kustija, jaja; Purnawan, Purnawan (Universitas Pendidikan Indonesia, 2021)
The purpose of this research is to determine the effect of the application of android-based media Smart with Pneumatics V.1.0 on student learning outcomes on the pneumatic component mechanism material. “Smart with Pneumatics V.1.0” is a learning media in the form of an Android-based computer program. This study uses a pre experimental design research method with the form of the research design used is one group pretest posttest design. The population used was students who contracted Pneumatics and Hydraulics courses in the even semester of the 2020/2021 academic year as many as 63 students. The conclusion of this study is that there is a significant influence in the application of android-based media